Case Report: Vemurafenib Treatment in Brain Metastases of BRAFS365L-Mutant Lung Papillary Cancer by Genetic Sequencing of Cerebrospinal Fluid Circulating Tumor DNA Detection - Jiang, Jianing; Gao, Jinqi; Wang, Gang; Lv, Jinyan; Chen, Wenting; Ben, Jing; Wang, Ruoyu (Frontiers in Oncology, 2021)
BRAF mutations, primarily sensitizing mutations, such as BRAFV600E, have been proven to response to the BRAF inhibitor, Dabrafenib combined with trametinib therapy, but there have been no data demonstrating that it has activity against NSCLC-related brain metastases (BM). How patients harboring BRAFS365L mutation (a rare mutation following BRAFV600E-inhibitor treatment) in NSCLC is unknown. Vemurafenib, another BRAF inhibitor, can reverse the resistance that develops with the BRAFS365L mutation following dabrafenib combined with trametentinib treatment in melanoma, but none has been reported in NSCLC. Lung papillary cancer, as a rare typing, occupies about 4% of NSCLC. Hence, we reported the first case of a patient with BM of lung papillary carcinoma harboring a BRAFV600E mutation who benefited from dabrafenib combined with trametinib, and following the development of the BRAFS365L mutation, vemurafenib remained an effective therapeutic option. Moreover, we found that the next-generation sequencing (NGS) of cerebrospinal fluid (CSF) circulating tumor DNA (ctDNA) may potentially provide more accurate information about intracranial lesions than ctDNA in the blood serum, which will be a better detection method.